State capacity and rule of law: the case of Upper Egypt - Abu Zahra, Reem (AUC Knowledge Fountain, 2011)
Governability or social order is a multi-faceted phenomenon where different actors, state, society and ruling regime, interact on daily basis. Sometimes, it is the regime that is blamed for the weak intensity of governance. Sometimes, it is the cultural setting and social norms that are accused of being anti-state. Culture in Upper Egypt has always been blamed for the inability of the police force to penetrate society and uphold rule of law. This piece of research tackled the phenomenon of tha'r as part of a bigger phenomenon of informal means of conflict resolution and the weak state penetration in society. The essence of "statenessÃƒÂ¢ is its ability to enforce rule of law. Resorting to informality is a regime strategy to weaken the state. The regime compromised the role of the when it, first, it gave more power to customary forms of conflict resolution despite Egypt's long legal and constitutional heritage. Second, it weakened the police force from the inside in ways that affected its ability perform its duty. Third, it made the security institution assume a political role in service of the ruling regime instead of achieving security.